ПРОФЕСІЙНА САМОВИЗНАЧЕННІСТЬ МОЛОДІ ТА МОЖЛИВОСТІ ЇЇ РЕАЛІЗАЦІЇ: ВІД СУСПІЛЬНОГО ДОСВІДУ ДО ПРАКТИКИ СЬОГОДЕННЯ - Siry, Evgeny; Zaslavska, Lyudmyla (Zhytomyr Ivan Franko State University, 2024)
The material is devoted to the problems of professional certainty of young people and the possibilities of their professional self-realization. The article clarifies professional self-determination as a complex, multi-stage process of development of a young person. It integrally reflects a person's personal and social self-determination. It is shown that professional self-determination is a complex phenomenon, the vectors of which change under different conditions. It is shown that professional self-determination is a complex phenomenon, the vectors of development of which change under different conditions, depending on various systemic and situational social and institutional factors. A decisive role in professional choice is given to education, to which, accordingly, the question of its content is raised. Taking into account the social experience of researching this issue, the material presents an analysis of key research schools, the experience of which illuminates the relevant scientific picture of the content of professional certainty and its implementation. It is shown that in Ukraine, since the years of the USSR, a certain legacy of professional determination has been formed, according to which, without proper higher education, after graduating from high school in the professional field, young people have the minimal opportunity to realize themselves. It is shown that professional self-realization and professional self-determination are always in a dialectical relationship. This is confirmed - both from social experience and from the conclusions of the relevant research schools, which from their own positions investigated this "dialectical" problem. It is shown that professional self-realization and professional self-determination are always in a dialectical relationship for the same reasons - the influence of different configurations of various factors of a systemic and situational nature.  Self-realization in the profession is also a socio-cultural phenomenon that is closely related to a specific social situation under certain circumstances (time, place, conditions) and has an individual character. The main point of this process is the search for a professional image of "myself". These provisions in the system of regulation of the youth employment market should be taken into account in the position of the formation of the tool and the method of its self-organization, not a direct organization in its development.